Factores socioeconómicos que influyen en el consumo de sustancias psicoactivas ilícitas en estudiantes de undécimo grado de una institución educativa del distrito especial, turístico y cultural de Riohacha, La Guajira (2021)
The study that unfolds has the general purpose of analyzing the factors socioeconomic factors that influence the use of illicit psychoactive substances in eleventh grade students from the district's Almirante Padilla educational institution special, tourist and cultural of Riohacha, La Guajira. Regarding the research method It is of a qualitative approach, of an interpretive type, framed in the biographical method, in its life history version, inasmuch as it allowed the researchers to interpret the story of the subjects interviewed the information was obtained through in-depth interviews with three (3) key informants, in this case the teachers who work in the educational institution Almirante Padilla linked with eleventh grade high school students general. The reliability of the sample is relative, using a qualitative study through of a triangulation.